Τρόποι αντιμετώπισης υγρασιών σε διατηρητέα κτίρια - Αναστασίου, Κωνσταντίνα (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
This thesis study aims to present the techniques used to solve the moisture problems in traditional settlements in Cyprus. Firstly, it refers to the way old people used to build their buildings in Cyprus. Subsequently, presents how moisture can enter a building and the problems that it may cause to a traditional settlement. Then, describes the techniques that builders used to prevent moisture penetration in their traditional buildings at the construction phase, also, presents the maintenance measures that owners used to take to maintain the techniques that were used at the construction phase. Furthermore, describes the techniques and the building materials that are used nowadays to stop the moisture penetration. At the end, are presented three real applications of some of the techniques that were referred in this thesis study. The first case is about a listed building in Limassol Centre. The other real case is about the restoration of a Neoclassical building in Nicosia that will houses the offices of the Cyprus’s Department of town planning and housing and the last real case is about Saint Nicolas monastery in Achaea, Greece.
Keywords: Moisture Problems; Moisture; Προβλήματα Υγρασίας; Υγρασία; Διατηρητέα Κτίρια